2012
DOI: 10.1039/c1dt11677k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, physicochemical properties and antioxidant activity of deferiprone-cyclodextrin conjugates and their iron(iii) complexes

Abstract: 3-Hydroxy-1,2-dimethylpyridin-4(1H)-one (deferiprone) is a successful iron chelator, which has been widely investigated for its activity in mitigating iron overload and in protecting against oxidative stress due to Reactive Oxygen Species (ROS). Herein, we present the synthesis, characterisation, physicochemical properties and antioxidant activity of two novel bioconjugates of β-cyclodextrin bearing the deferiprone moiety either on the upper rim (1) or on the lower rim (2) of the cyclodextrin and their iron(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 38 publications
(33 reference statements)
4
29
0
Order By: Relevance
“…This behavior has been generally reported for functionalized CyDs and is due to the interaction of the functionalizing moiety with CyD. The addition of ADM did not significantly influenced CD signals at variance of CyD systems in which the pendant is included . The data further confirm the lid‐type geometry of IOX moiety as encapsulation of small molecules (ADM) into the cavity is not expected to affect this type of conformation.…”
Section: Resultssupporting
confidence: 82%
“…This behavior has been generally reported for functionalized CyDs and is due to the interaction of the functionalizing moiety with CyD. The addition of ADM did not significantly influenced CD signals at variance of CyD systems in which the pendant is included . The data further confirm the lid‐type geometry of IOX moiety as encapsulation of small molecules (ADM) into the cavity is not expected to affect this type of conformation.…”
Section: Resultssupporting
confidence: 82%
“…Compound 3 also has a moderate affinity for Cu 2+ as demonstrated by the value of 18.8 for log β (CuL), and 23.9 for log β 2 (CuL 2 ) reported elsewhere . As observed for iron, we anticipate the conjugation with CyD does not significantly modify the copper‐binding ability of the chelators . Moreover, we confirmed through UV/Vis and CD spectroscopy that both derivatives maintain the ability of 3 to complex copper ions.…”
Section: Resultssupporting
confidence: 84%
“…In the case of 2 , the hydroxy groups may be less available to react with the radical cation, probably due to the higher rigidity of the system relative to the analogous 6‐functionalized derivative. Similar behavior has also been reported for related cyclodextrin–deferiprone conjugates . However, the ability of 2 to scavenge free radicals is much higher than that of Trolox.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Polymorphic forms exhibit differences with respect to bioavailability, solubility and the stability of the crystalline forms (Yu et al, 2003), and influence the pharmacokinetics and pharmacodynamics of a drug administered into the body (Singhal & Curatolo, 2004). The Cambridge Structural Database (CSD; Groom et al, 2016) was searched for deferiprone (3-hydroxy-1,2-dimethylpyridin-4-one), (I) (see Scheme), and it was found that there are more metal complexes of deferiprone (Ahmed et al, 2000;Drouza et al, 2004;Puglisi et al, 2012;Wang et al, 2018). It exists in five polymorphic forms (, , , and "), of which the from is the thermodynamically more stable and commercially marketed, whereas the and forms exhibit better bioavailability (Censi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%